Cardiac autonomic responses of trained cyclists at different training amplitudes - Picanço, L. M.; Cavalheiro, G.; Vaz, M. S.; Del Vecchio, F. B. (Archivos de medicina del deporte, 2017)
Purpose: The aim of this study was to evaluate the effect of different training amplitudes on the autonomic nervous system (ANS) responses and recovery through heart rate (HR), heart rate variability (HRV) and rate of perceived effort (RPE).